Labor Market Power, Self-Employment, and Development - Francesco Amodio; Pamela Medina; Monica Morlacco (Institute of Labor Economics (IZA), 2022)
This paper shows that self-employment opportunities shape the market power of employers in low-income countries, with implications for industrial development. Using data from Peru, we document substantial employer concentration and high self-employment rates across manufacturing local labor markets. Where employer concentration is higher, wages are lower, and self-employment is more prevalent but less remunerative. To interpret these facts, we build a general equilibrium model where labor market power in each market arises from (i) strategic interactions among employers and (ii) sorting of heterogeneous workers across wage work and self-employment. We structurally estimate the model and quantify the relevance of these mechanisms for rent-sharing between workers and firms and for the effect of policies promoting manufacturing wage employment. We show that changes in concentration magnify the pass-through of productivity and profitability shocks to wages, but worker sorting across wage and self-employment mitigates these effects. We find that policies that increase firm productivity are more effective in expanding wage employment and increasing workers' earnings than other interventions that improve workers' skills or decrease firm entry cost.
Keywords: J2; J3; J42; L10; O14; O54; 330; labor market power; monopsony; self-employment; sorting; development